Roflumilast reduces the number of lung adenocarcinomas, inflammation, and emphysema in a smoking-induced mouse model - Kaori Sakurai; Shingo Nakayama; Shotaro Chubachi; Shiro Otake; Takashi Shimada; Hidehiro Irie; Akihiro Tsutsumi; Naofumi Kameyama; Ahmed E. Hegab; Masayuki Shimoda; Junko Hamamoto; Hideki Terai; et al. (BMC Pulmonary Medicine)
Abstract Background The prognosis of lung cancer complicated by chronic obstructive pulmonary disease is poor, and effective prophylactic agents have not been established. Given that inflammation is a shared pathogenic mechanism of both diseases, we aimed to evaluate the efficacy of roflumilast, a novel anti-inflammatory drug, in preventing emphysema and lung cancer using a smoking-induced lung cancer mouse model. Methods Male A/J mice were exposed to 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone, a potent carcinogen, and intermittent mainstream cigarette smoke for 20 weeks. Roflumilast or vehicle was administered via intragastric gavage once daily. Lung tissues were assessed for tumor nodules and emphysema, and bronchoalveolar lavage fluid was collected for cell counting. Emphysema severity and concentrations of inflammatory cytokines (IL-6, IL-1β, and TNF-α) were assessed. RAW 264.7 macrophage cells were used to assess cellular responses to cigarette smoke extract. Results Roflumilast attenuated the increase in total cells and macrophages in bronchoalveolar lavage fluid induced by intermittent smoking exposure and significantly suppressed smoking-induced expressions of IL-6, IL-1β, and TNF-α. Roflumilast also reduced emphysematous changes and the number of lung tumors. In vitro, roflumilast attenuated cigarette smoke extract-induced expression of IL-6, IL-1β, and TNF-α in RAW 264.7 cells. Conclusions This study highlights the potential use of roflumilast as a chemopreventive agent for patients with chronic obstructive pulmonary disease who are at risk of lung cancer and underscores its relevance for future clinical application and research on phosphodiesterase-4 inhibitors.